Temporal characterization of biogas slurry: a pre-requisite for sustainable nutrigation in crop production - Yadav, Rashmi; Sudhishri, Susama; Khanna, Manoj; Lal, Khajanchi; Dass, Anchal; Kushwaha, H. L.; Bandyopadhyay, Kalikinkar; Dey, Abir; Kushwah, Ajay; Nag, Ramineni Harsha (Frontiers in Sustainable Food Systems, 2023)
Biogas slurry serves as a useful organic fertilizer due to its substantial nutritional content, and its characterization enables the evaluation of nutrient content and its efficient utilization. This study focuses on the nutrient content variations in biogas slurry from different dairy farm systems located near ICAR-Indian Agricultural Research Institute (IARI) (New Delhi), Daryapur Kalan (New Delhi), and Madanpur (Uttar Pradesh) across pre-monsoon, monsoon, and post-monsoon seasons. The study reveals significant variations in macro-nutrient levels, particularly nitrogen (N), which showed variations exceeding 3% and a wider range of almost 6% during the pre-monsoon and post-monsoon periods. Spatial differences between dairy farms also contributed to the variance, with over a 10% difference observed between IARI and Daryapur Kalan, as well as between IARI and Madanpur. Phosphorus (P) remained stable across seasons with spatial variations, while potassium (K) exhibited a reverse trend. Correlation analysis highlighted strong positive associations between N content and phosphorus (0.959), organic